Salt Eustress Induction in Red Amaranth (Amaranthus gangeticus) Augments Nutritional, Phenolic Acids and Antiradical Potential of Leaves - Umakanta Sarker; Sezai Ercisli (MDPI AG, 2022)
Earlier researchers have highlighted the utilization of salt eustress for boosting the nutritional and phenolic acid (PA) profiles and antiradical potential (ARP) of vegetables, which eventually boost food values for nourishing human diets. Amaranth is a rapidly grown, diversely acclimated C4 leafy vegetable with climate resilience and salinity resistance. The application of salinity eustress in amaranth has a great scope to augment the nutritional and PA profiles and ARP. Therefore, the A. gangeticus genotype was evaluated in response to salt eustress for nutrients, PA profile, and ARP. Antioxidant potential and high-yielding genotype (LS1) were grown under four salt eustresses (control, 25 mM, 50 mM, 100 mM NaCl) in a randomized completely block design (RCBD) in four replicates. Salt stress remarkably augmented microelements, proximate, macro-elements, phytochemicals, PA profiles, and ARP of A. gangeticus leaves in this order: control < low sodium chloride stress (LSCS) < moderate sodium chloride stress (MSCS) < severe sodium chloride stress (SSCS). A large quantity of 16 PAs, including seven cinnamic acids (CAs) and nine benzoic acids (BAs) were detected in A. gangeticus genotypes. All the microelements, proximate, macro-elements, phytochemicals, PA profiles, and ARP of A. gangeticus under MSCS, and SSCS levels were much higher in comparison with the control. It can be utilized as preferential food for our daily diets as these antiradical compounds have strong antioxidants. Salt-treated A. gangeticus contributed to excellent quality in the end product in terms of microelements, proximate, macro-elements, phytochemicals, PA profiles, and ARP. A. gangeticus can be cultivated as an encouraging substitute crop in salt-affected areas of the world.